Magnetic Fields and Accretion Processes in Young Stars: A case study of the classical T Tauri star DK Tau - Nelissen, Marie (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
Low-mass young stars that are a few million years old and called classical T Tauri stars (cTTs) experience magnetospheric accretion. They are surrounded by a circumstellar disk (which consists of an inner and outer disk) and accrete matter from it thanks to their magnetic fields. When the matter falls onto the star, it produces an accretion shock, which generates veiling in the stellar spectra. The shock also causes an accretion spot on the stellar surface. Misalignments between the stellar rotation axis and the outer disk axis are not predicted by standard theories of stellar formation, yet have been observed in several cTTs. This thesis studies one cTTs in particular, DK Tau, which is suspected of being among them. Additionally, it is an excellent subject to investigate the interaction between stellar magnetic fields and material accreting from the circumstellar disk, since it displays clear signatures of accretion. Focusing on a single object allows one to uncover the physics that governs its behavior, and the values derived from its analysis are important to constrain the models of star formation. One goal of this thesis is to study DK Tau's average line-of-sight magnetic field in both photospheric absorption lines and accretion-powered emission lines. The second is to examine inconsistencies regarding the inclination of its rotation axis. The third aim is to investigate the accretion, particularly the mass accretion rate, using two different methods for comparison purposes. The last objective is to carry out a preliminary study of its large-scale magnetic field configuration. For these purposes, archival data from the CFHT/ESPaDOnS and TBL/NARVAL spectropolarimeters were used. The observations probe two distinct epochs (i.e. 2010 and 2012), allowing one to study the evolution of DK Tau over time. Each dataset spans a few stellar rotation cycles and covers the optical range. First, stellar parameters were determined. Next, the veiling was measured across the spectra and its effects were removed. Then, least-squares deconvolution profiles of the photospheric absorption lines were obtained, before determining the average line-of-sight magnetic field from them. In addition, accretion-powered emission lines were investigated as tracers of the magnetic fields present in the accretion shocks. Next, the accretion luminosity was derived from multiple accretion-powered emission lines. This was done in order to calculate the mass accretion rate. This value was then compared to the one calculated from the fitting of accretion shock models onto the values of veiling. Finally, Zeeman-Doppler Imaging was applied to the photospheric absorption lines, in order to derive a first estimate of the photospheric brightness distribution and magnetic field configuration. It was found that peak values of the veiling (defined as the ratio between the accretion shock and photospheric fluxes) range from 0.2 to 1.8, with a steeper trend across the wavelength range for higher peak values. DK Tau shows a magnetic obliquity of ~20?. Based on the HeI line, in 2010, the average line-of-sight magnetic field reaches up to 1.77 kG. In 2012, it reaches up to 1.99 kG. The stellar rotation axis is inclined by 58? (+18)(-11), which is significantly different from the outer disk axis inclination of 21? given in the literature. Regarding the mass accretion rate, when using the accretion-powered emission lines, its values range from log(Macc[Msol/yr]) = -8.20 to log(Macc[Msol/yr]) = -7.40. This agrees with the values found in the literature, as well as the values calculated using the accretion shock models and the veiling. Moreover, a power-law correlation between the values of the accretion luminosity and the optical veiling is identified. In conclusion, DK Tau's outer disk axis is likely misaligned compared to its rotation axis. In addition, both procedures of determining the mass accretion rate provide similar results. Furthermore, the correlation between the accretion luminosity and the veiling provides a helpful method of confirming accretion luminosity values by measuring the veiling at a single wavelength in the optical.
APPROVED
Keywords: astrophysics; star formation; T Tauri stars; magnetic field; accretion; spectropolarimetry